PRODUCTION AND CHARACTERIZATION OF RECOMBINANT ALPHA-AMYLASE SACCHAROMYCOPSIS FIBULIGERA R64 EXPRESSED IN PICHIA PASTORIS - Sanawati (NIM 105 03 058), Anna
ABSTRACT: Alpha-Amylase is an endoacting enzyme which hydrolyses alpha-1,4 glycosidic linkages of the polysaccharides into soluble maltooligosaccharide, maltodextrin, and small quantity of glucose. Alpha-Amylase has been used in various industries, such as starch processing, textile, bakery, and pharmacy. A commercial production of α-amylase in industry requires an efficient cell factory capable of producing alpha-amylase at very high level. Pichia pastoris expression system offers several advantages, such as high secretion efficiency, high cell density, and inexpensive culture media, which will result in the cost effective α-amylase production. This research describes heterologous expression of Saccharomycopsis fibuligera R64 alpha-amylase gene (ALP1) in P. pastoris, including determination of optimal production condition and influence of introduction of new disulphide bond between A and C domains to ALP1 stability. ALP1 and alp1 gene had been cloned into pPICZ alphaA and P. pastoris KM71H had been transformed by the resulted recombinant plasmid. ALP1 and alp1 fused with methanol inducible AOX1 promoter. The alpha-amylase activity was monitored after 24, 48, 72, 96, 120, and 144 hours of growth in the media containing 0.5% (v/v) of methanol and it was found that the optimal induction time was 96 hours. Alpha-Amylase secretion increased dramatically with activity of 8.2 x 10 5 U/ml upon the addition of methanol to a final concentration of 4% (v/v) for 96 hours. Characterization of ALP1 and alp1 showed that optimum pH and optimum temperature for both enzymes are 5.5 and 50 oC. However, the alp1 mutant still retains 96% activity at 60 oC at which temperature the wild type activity was only 78% of original activity. In silico analysis of structure modeling showed that structure of ALP1 is more rigid than alp1, but total energy data showed that alp1 (-20270,895 kJ/mol) has lower total energy than ALP1 (-20179,084 kJ/mol), indicating that alp1 has higher stability than ALP1.